Teknik Supervisi Individual: Peningkatan Kompetensi Guru MI dalam Membuat Media Pembelajaran dengan Paint dan Power Point di MIN 7 dan MI Yappi Semoyo Patuk Gunungkidul - Karmanto Karmanto (Jurnal Pendidikan Madrasah, 2021)
This research aims to find out the ability of Madrasah Ibtidaiyah teachers in making simple learning media with paint and power points for the teaching and learning process. The ability of teachers in making learning media can make it easier to achieve learning goals as specified in the learning implementation plan. This research uses action research methods and is carried out in two cycles. The results showed that individualized supervision techniques are one form of assistance focused on individual activities related to improving the quality of learning. The implementation of supervise conducted with guidance and training can improve the teacher's ability to create learning media with paint and power points. In cycle I, of the 8 teachers who were objected, 3 teachers or 37.50% were sufficiently cryptic and 5 teachers or 62.50% were less cryptic. The cycle I average value of 66.88 increased in cycle II to 84.58 or increased by 27.66%. After being given action on cycle II the ability of 8 teachers to make learning media with paint and power paint to 100%, 7 teachers got good criteria, one of which with very good criteria with a score of 92.78 or 12.50%.